2013
DOI: 10.1007/s11432-013-4887-5
|View full text |Cite
|
Sign up to set email alerts
|

A memristor-based architecture combining memory and image processing

Abstract: Color image edge extraction using memristor-based CNN SCIENTIA SINICA Informationis 47, 863 (2017); Fixed-time synchronization of delayed memristor-based recurrent neural networks SCIENCE CHINA Information Sciences 60, 032201 (2017); Exponential stabilization of memristor-based neural networks with unbounded time-varying delays SCIENCE CHINA Information Sciences 64, 189205 (2021);. RESEARCH PAPER. SCIENCE CHINA Information Sciences

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
2
16
0
1
Order By: Relevance
“…l(b), if memristor Q is reset to 0 before IMP operation, the circuit will implement NOT operation, that is, q=�p. Truth table of IMP operation With the similar circuit and analysis method, we found that with different stimulating voltages, the circuit could finish AND operation [10], as shown in Fig. 2(a).…”
Section: The Basic Logic Circuits With Memristorsmentioning
confidence: 99%
“…l(b), if memristor Q is reset to 0 before IMP operation, the circuit will implement NOT operation, that is, q=�p. Truth table of IMP operation With the similar circuit and analysis method, we found that with different stimulating voltages, the circuit could finish AND operation [10], as shown in Fig. 2(a).…”
Section: The Basic Logic Circuits With Memristorsmentioning
confidence: 99%
“…window/neighborhood selection 9: DImg = |window − window(w r + 1, w r + 1)| difference/distance image 10: windowM ask = DImg ≤ η Variable Pixel G-Neighbors are those with value1 11: N Zcount = countN onZeros(windowM ask) counting G-Neighbors 12: F (r − w r , c − w r ) = sum(window. * windowM ask)/N Zcount pixel-to-pixel masking and output calculation 13: end for 14: end for 15: end function lying on the nonlinear and variable characteristics of the memristor [23,24].…”
Section: Neuromorphic Circuits Using Memristorsmentioning
confidence: 99%
“…基于单个忆阻器用于图像存储的忆阻交叉阵列 [11,23] , 改进了交叉点上忆阻器结构. 将突触设计 电路放置在交叉点上, 如图 5 所示,它包含 4×4 交叉阵列、电压转换器、行列开关选择器、读写控制 杨玖等: 一种反向串联忆阻突触电路的设计及应用 图 4 生物学动作电位对应的 STDP 学习函数 2) 读入灰度图像.…”
Section: 突触电路用于交叉阵列的结构及设计步骤unclassified